Evaluating the processed beans of different cocoa (Theobroma cacao L.) accessions for quality parameters - V. Jegadeeswari, K. Arunkumar (Journal of Phytology, 2019)
The objective of this study was to evaluate the variability in quality parameters of different identified cocoa plus trees from Coimbatore district in Tamil Nadu. Thirty five (35) plus trees in two different farmers field were evaluated for their quality traits. The quality parameters like fat content (%), carbohydrate content (mg/g), protein content (mg/g), theobromine content (mg/g), caffeine content (mg/g), catechin content (mg/g) and caffeic acid content (mg/g). A rapid method like high performance liquid chromatography (HPLC) method is used for the determination of theobromine, caffeine, catechin and caffeic acid in cocoa beans. Among the 35 plus trees evaluated for bean quality, highest fat content was recorded in Tc (Vedapatti) 94, while highest carbohydrate content was recorded in Tc (Vedapatti) 64 and highest protein content was recorded in Tc (Vedapatti) 76. The highest theobromine was recorded in Tc (Vedapatti) 63, caffeine was recorded in Tc (Vedapatti) 91, while the amount of caffeic acid and catechin was the highest in Tc (Vedapatti) 76. This evaluation study showed wide variation for quality parameters. These variability may be used in further breeding program enhance the quality traits and improve flavours of the final product.